2006
DOI: 10.1002/dmrr.645
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol oxides as biomarkers of oxidative stress in type 1 and type 2 diabetes mellitus

Abstract: ChOx are suitable biomarkers of oxidative stress and may be useful in clinical studies to follow drug effects on lipid oxidative modifications in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 37 publications
1
58
0
3
Order By: Relevance
“…In obese type 2 diabetic patients, plasma 9-and 13-HODE levels are decreased by troglitazone therapy (46), but no information is available regarding plasma or lipoprotein-related HODE concentrations in T1DM. However, Ferderbar et al (47) recently reported significant increases in total cholesterol oxides and 7-hydroxycholesterol in plasma of children and young adults with T1DM, even in the absence of hypercholesterolemia. Martin-Gallan et al (48) have also reported increased levels of LPOs and the lipid peroxidation product, malondialdehyde, in plasma of T1DM patients, independent of complication status.…”
Section: Discussionmentioning
confidence: 97%
“…In obese type 2 diabetic patients, plasma 9-and 13-HODE levels are decreased by troglitazone therapy (46), but no information is available regarding plasma or lipoprotein-related HODE concentrations in T1DM. However, Ferderbar et al (47) recently reported significant increases in total cholesterol oxides and 7-hydroxycholesterol in plasma of children and young adults with T1DM, even in the absence of hypercholesterolemia. Martin-Gallan et al (48) have also reported increased levels of LPOs and the lipid peroxidation product, malondialdehyde, in plasma of T1DM patients, independent of complication status.…”
Section: Discussionmentioning
confidence: 97%
“…In this study we found that both Lxrα and Lxrβ mRNA was present and significantly upregulated by the addition of LXR agonists to beta cells, suggesting that LXR elevation might be involved in pancreatic beta cell dysfunction in type 2 diabetes. Moreover, levels of oxysterols, endogenous activators of LXRs, are markedly upregulated in the blood plasma of patients with type 2 diabetes [34,35]. Importantly, Mitro et al [36] demonstrated that glucose also activates LXRs at physiological concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma of patients with DM has been studied, and the oxysterols 7␣-and 7␤-OH-Ch, and 5␣,6␣-and 5␤,6␤-epoxy-Ch were measured. These oxysterols increased in the DM plasma, and these oxysterols have been suggested to be useful as biomarkers for oxidative damage in patients with DM (28).…”
Section: Nonenzymatically Formed Oxysterols In Pathophysiologymentioning
confidence: 98%